Agricultural Potensial of Binusan Village, Nunukan Sub-District, Nunukan District, North Kalimantan Province - Hidayat, Nur; Dewi, Candra; Nuzula, Nila Firdauzi; Susenohaji, Susenohaji (University of Brawijaya, 2018)
Agricultural potential in underdeveloped villages has not been mapped so that it is difficult to be used as a reference in development programs. The purpose of this research is to know the potential of agriculture in Binusan Village. The method used is qualitative approach with descriptive data analysis. The results of the research show that the main potentials in Binusan village are seaweed and oil palm